Exploring the Effect of Maximum Cure Temperature on the Thermal and Thermomechanical Properties of Polybenzoxazine Networks. Issue 1 (23rd August 2013) - Jungman, Matthew J.; Cobb, Jared S.; Lawler, Daniel J.; Sholar, Jamie D.; Johnson, Charles B.; Patton, Derek L.; Bowman, Christopher N.; Horkay, Ferenc
Summary The thermal and thermomechanical properties of two commercially available polybenzoxazine materials were investigated as a function of maximum temperature employed in the cure profile. Cationic ring‐opening polymerization of Araldite 35600 and Araldite 35900 was carried out at 180 °C, 200 °C, 220 °C, and 240 °C. FTIR and differential scanning analysis results show maximum conversion in each monomer system is achieved at 180 °C or 200 °C, and that higher cure temperatures were unnecessary. Thermal stability of the polybenzoxazine materials prepared under both low and high temperature cure profiles, as indicated by thermogravimetric analysis results, was minimally affected with increasing cure temperatures. Dynamic mechanical analysis results indicate that despite an increase in the rubbery storage modulus as a function of maximum cure temperature, higher cure temperatures employed in ambient atmosphere ovens result in detrimental effects on the glass transition temperature of the network. In the case of Araldite 35600, a 12 °C decrease in Tg was observed when the cure temperature was increased from 180 °C to 240 °C. The combined FTIR, DSC, and DMA data for Araldite 35600 and Araldite 35900 show that optimized conversion and thermomechanical properties can be achieved at lower cure temperatures. Thus, a judicious choice of cure profile must be considered to avoid degradative processes and to achieve the maximum properties of polybenzoxazine systems.